The influences of celebrity endorsements on consumers' purchase intentions toward sports equipment - Chong, Wei Ni (2024)
First of all, the research problem is the lack of investigation into the influences of celebrity endorsements on Malaysian consumers’ purchase intentions, especially toward sports equipment. Next, the research objectives and research questions of this study are to determine the relationship between the influences of celebrity endorsements and consumers' purchase intentions toward sports equipment and to examine whether the influences of celebrity endorsements affect consumers' purchase intentions toward sports equipment. Besides, this study adopts the Theory of Planned Behavior (TPB) to predict consumers' behavioral intentions, with four independent variables (source credibility, source attractiveness, meaning transfer model, and product-celebrity match-up) and one dependent variable (purchase intention). In addition, a proposed conceptual framework and four hypotheses are developed. Furthermore, there are several studies that support the hypotheses proposed in this study. Additionally, Malaysians aged 18 to 64 were also targeted. Apart from this, this study also used quantitative research methods, questionnaire survey methods, and IBM Statistical Package for Social Sciences (SPSS) statistical software to collect and analyze data. Other than this, source credibility, source attractiveness, and product-celebrity match-up have a statistically significant influence on consumers' purchase intentions; however, the impact of the meaning transfer model on consumers' purchase intentions is not statistically significant. Therefore, H1, H2, & H4 are supported; however, H3 is rejected. Moreover, this study will also benefit businessmen or marketers who want to utilize celebrity endorsement as a marketing strategy. In addition to this, this study recommends expanding the target population and geographical scope, exploring other suitable independent variables, and focusing on athletes' endorsements toward sports equipment for future research.